2019
DOI: 10.1007/s10552-019-01145-7
|View full text |Cite
|
Sign up to set email alerts
|

“My husband says this: If you are alive, you can be someone…”: Facilitators and barriers to cervical cancer screening among women living with HIV in India

Abstract: Purpose: Women living with human immunodeficiency virus (WLWH) have a higher risk of cervical cancer than women without HIV. In addition, women in India experience a high burden of death from cervical cancer. This qualitative study evaluated individual and interpersonal factors influencing cervical cancer screening among WLWH in Surat, India. Methods:In-depth interviews were conducted with 25 WLWH and 15 stakeholders in Surat, India. Data were analyzed using directed content analysis to identify individual and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…, 2016 ), while several articles suggested that the fear of screening results was a barrier to undergoing screening. In one of the studies from India, more than 75% of the women who were interviewed feared the Pap smear and the subsequent results ( Kung et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2016 ), while several articles suggested that the fear of screening results was a barrier to undergoing screening. In one of the studies from India, more than 75% of the women who were interviewed feared the Pap smear and the subsequent results ( Kung et al. , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Family support is also essential and required for women of reproductive age who wish to undergo an examination and those suffering from breast or cervical cancer (Kung et al, 2019;Rasul et al, 2015). It is similar to Azriful's research from 2021, which explains that family support is a cue to action that causes a person to live a healthy life.…”
Section: Social Support For Early Detectionmentioning
confidence: 99%